Evaluation of human-baited double net trap and human-odour-baited CDC light trap for outdoor host-seeking malaria vector surveillance in Kenya and Ethiopia - Degefa, Teshome (Malar J, 2020)
BACKGROUND: Surveillance of outdoor host-seeking malaria vectors is crucial to monitor changes in vector biting behaviour and evaluate the impact of vector control interventions. Human landing catch (HLC) has been considered the most reliable and gold standard surveillance method to estimate human-biting rates. However, it is labour-intensive, and its use is facing an increasing ethical concern due to potential risk of exposure to infectious mosquito bites. Thus, alternative methods are required. This study was conducted to evaluate the performance of human-odour-baited CDC light trap (HBLT) and human-baited double net trap (HDNT) for outdoor host-seeking malaria vector surveillance in Kenya and Ethiopia. METHODS: The sampling efficiency of HBLT and HDNT was compared with CDC light trap and HLC using Latin Square Design in Ahero and Iguhu sites, western Kenya and Bulbul site, southwestern Ethiopia between November 2015 and December 2018. The differences in Anopheles mosquito density among the trapping methods were compared using generalized linear model. RESULTS: Overall, 16,963 female Anopheles mosquitoes comprising Anopheles gambiae sensu lato (s.l.), Anopheles funestus s.l., Anopheles pharoensis, Anopheles coustani and Anopheles squamosus were collected. PCR results (n = 552) showed that Anopheles arabiensis was the only member of An. gambiae s.l. in Ahero and Bulbul, while 15.7% An. arabiensis and 84.3% An. gambiae sensu stricto (s.s.) constituted An. gambiae s.l. in Iguhu. In Ahero, HBLT captured 2.23 times as many An. arabiensis and 2.11 times as many An. funestus as CDC light trap. In the same site, HDNT yielded 3.43 times more An. arabiensis and 3.24 times more An. funestus than HBLT. In Iguhu, the density of Anopheles mosquitoes did not vary between the traps (p > 0.05). In Bulbul, HBLT caught 2.19 times as many An. arabiensis as CDC light trap, while HDNT caught 6.53 times as many An. arabiensis as CDC light trap. The mean density of An. arabiensis did not vary between HDNT and HLC (p = 0.098), whereas the HLC yielded significantly higher density of An. arabiensis compared to HBLT and CDC light trap. There was a significant density-independent positive correlation between HDNT and HLC (r = 0.69). CONCLUSION: This study revealed that both HBLT and HDNT caught higher density of malaria vectors than conventional CDC light trap. Moreover, HDNT yielded a similar vector density as HLC, suggesting that it could be an alternative tool to HLC for outdoor host-seeking malaria vector surveillance.